Elevated temperature and CO2 cause differential growth stimulation and drought survival responses in eucalypt species from contrasting habitats. (16th December 2019) - Apgaua, Deborah M G; Tng, David Y P; Forbes, Samantha J; Ishida, Yoko F; Vogado, Nara O; Cernusak, Lucas A; Laurance, Susan G W
Abstract: Climate change scenarios predict increasing atmospheric CO2 concentrations ([CO2 ]), temperatures and droughts in tropical regions. Individually, the effects of these climate factors on plants are well established, whereas experiments on the interactive effects of a combination of factors are rare. Moreover, how these environmental factors will affect tree species along a wet to dry gradient (e.g., along tropical forest–savanna transitions) remains to be investigated. We hypothesized that under the simulated environmental conditions, plant growth, physiological performance and survivorship would vary in a manner consistent with the species' positions of origin along this gradient. In a glasshouse experiment, we raised seedlings of three Eucalyptus species, each occurring naturally in a wet forest, savanna and forest–savanna ecotone, respectively. We evaluated the effect of drought, elevated temperature (4 °C above ambient glasshouse temperature of 22 °C) and elevated temperature in combination with elevated [CO2 ] (400 ppm [CO2 ] above ambient of 400 ppm), on seedling growth, survivorship and physiological responses (photosynthesis, stomatal conductance and water-use efficiency). Elevated temperature under ambient [CO2 ] had little effect on growth, biomass and plant performance of well-watered seedlings, but hastened mortality in drought-affected seedlings, affecting the forest and ecotone more strongly than the savanna species. In contrast, elevated [CO2 ] in combination with elevated temperatures delayed the appearance of drought stress symptoms and enhanced survivorship in drought-affected seedlings, with the savanna species surviving the longest, followed by the ecotone and forest species. Elevated [CO2 ] in combination with elevated temperatures also enhanced growth and biomass and photosynthesis in well-watered seedlings of all species, but modified shoot:root biomass partitioning and stomatal conductance differentially across species. Our study highlights the need for a better understand of the interactive effects of elevated [CO2 ], temperature and drought on plants and the potential to upscale these insights for understanding biome changes.